2019
DOI: 10.1242/jcs.222372
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-dependent constraints drive remodeling of epithelia

Abstract: Epithelial tissues function as barriers that separate the organism from the environment. They usually have highly curved shapes, such as tubules or cysts. However, the processes by which the geometry of the environment and the cell's mechanical properties set the epithelium shape are not yet known. In this study, we encapsulated two epithelial cell lines, MDCK and J3B1A, into hollow alginate tubes and grew them under cylindrical confinement forming a complete monolayer. MDCK monolayers detached from the algina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
7
27
0
Order By: Relevance
“…Over a longer time period, cell monolayers detached, tore, and reorganized but never folded ( Figure S4). These results showed that when proliferation is blocked and contractility is not affected, monolayer detachment is observed, but not folding, supporting our previous findings that cell contractility is involved in detachment and not in folding (Maechler et al, 2019). It also shows that confinement is essential to folding.…”
Section: Epithelial Monolayer Folding Is Due To Bucklingsupporting
confidence: 89%
See 1 more Smart Citation
“…Over a longer time period, cell monolayers detached, tore, and reorganized but never folded ( Figure S4). These results showed that when proliferation is blocked and contractility is not affected, monolayer detachment is observed, but not folding, supporting our previous findings that cell contractility is involved in detachment and not in folding (Maechler et al, 2019). It also shows that confinement is essential to folding.…”
Section: Epithelial Monolayer Folding Is Due To Bucklingsupporting
confidence: 89%
“…These mechanisms are not exclusive to each other, and the relative contribution of each one may vary in different physiological conditions. For example, we previously identified that in our system, contractility of cells, together with the curvature of the alginate tube, was involved in releasing of adhesion but not in folding (Maechler et al, 2019). In the specific case of gastrulation, which our encapsulation assay intends to mimic, we imagine that apical constriction could set the position and the timing of the fold, and that buckling would drive the propagation of the invagination.…”
Section: Ll Open Accessmentioning
confidence: 98%
“…They showed that the monolayers of both cell lines detached from the tube; however, the J3B1A monolayer detached at a slower rate than the MDCK monolayer. This detachment was driven by cellular contractile stresses . The studies discussed above highlight that the cellular response toward substrate curvatures is highly dependent on both the characteristics of the cell (such as size and contractility) and the characteristics of the structure (size and geometry).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, renal tubules exhibit a convoluted shape of tubule, where this anatomical structure supports the functions of the kidney [26]. Recently, it has been reported that curved tubule induced the detachments of epithelial tissue cultured in alginate hollow tubule, and this propensity was more likely occurred when cells experienced high contractility and local curvature of the winding tubule [27]. However, it is still largely unexplored how the cells respond on out-of-plane geometry, even though it is essential as a cell-instructive material parameter.…”
Section: Introductionmentioning
confidence: 99%